Novel role for alpha-2-macroglobulin (A2M) as a disease modifying protein in senile osteoporosis - Boregowda, Siddaraju V.; Haga, Christopher L.; Supper, Valentina M.; Booker, Cori N.; Phinney, Donald G. (Frontiers in Cell and Developmental Biology, 2023)
In the rapidly aging U.S. population, age-induced bone loss (senile osteoporosis) represents a major public health concern that is associated with a significant increased risk for low trauma fragility fractures, which are debilitating to patients, cause significant morbidity and mortality, and are costly to treat and manage. While various treatments exist to slow bone loss in osteoporosis patients, these suffer from poor tolerability and label restrictions that limit their overall effectiveness. Over the past decade, skeletal stem/progenitor cells (SSPCs), which are the main precursor of osteoblasts and adipocytes in adult bone marrow (BM), have emerged as important players in osteoporosis. Herein, we identified alpha-2-macroglobulin (A2M), a pan-protease inhibitor that also binds inflammatory cytokines, as one of the most downregulated transcripts in SSPCs isolated from the BM of elderly (24month-old) vs. mature (3-month-old) mice. We further demonstrate that silencing of A2M expression in human BM-derived mesenchymal stem cells (BM-MSCs) induced their proliferation and skewed their lineage bifurcation toward adipogenesis at the expense of osteogenesis thereby recapitulating critical aspects of age-induced stem cell dysfunction. Together, these findings identify A2M as a novel disease modifying protein in osteoporosis, downregulation of which in bone marrow promotes SSPC dysfunction and imbalances in skeletal homeostasis.